Towards Effective Social Insurance in Latin America: The Importance of Countercyclical Fiscal Policy - Miguel Braun; Luciano di Gresia (Inter-American Development Bank, Research Department, 2003)
Latin America is a volatile, crisis-prone region, with limited and inadequate social insurance. Therefore, the long-term as well as the recent poor suffer significantly during crises. Furthermore, social spending is procyclical in the region, but less so than total spending, indicating that the effectiveness of compensatory social policies designed to protect those vulnerable to crises is constrained by adjustments during recessions. The causes of procyclical fiscal policy lie in the political constraints on saving during expansions, combined with limited creditworthiness during recessions, and enhanced by economic volatility and a low share of automatic stabilizers in the budget. We evaluate policy options to reduce procyclicality of fiscal policy, such as stabilization funds, fiscal rules and reform of budget institutions, and argue in favor of integrated policy proposals based on more country-specific analysis, such as the Fiscal Responsibility Law in Brazil.
Keywords: E62; H62; 330; Fiscal policy; social policy; procyclicality; Latin America; Finanzpolitik; Antizyklische Finanzpolitik; Öffentliche Sozialausgaben; Lateinamerika